2001
DOI: 10.1097/00004770-200104000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Stafne’s Bone Cavity in the Anterior Mandible: A Possible Diagnostic Challenge

Abstract: Stafne was the first to report the presence of "bone cavities" in the angle of 35 mandibles. Such cavities generally appear in the area between the mandibular first molar and the mandibular angle, and are not considered rare. One of their primary radiological diagnostic features is the characteristic location below the mandibular canal. Stafne's bone cavity is relatively rare in the anterior mandible. The mandibular canal is not present in the anterior mandible. As a result, diagnosis in the anterior mandible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0
10

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 8 publications
0
46
0
10
Order By: Relevance
“…Should contrast material be administered, the salivary gland contents of a Stafne bone cavity should enhance to the same degree as the adjacent submandibular gland. 9,12,13 Sialography may also be considered owing to the salivary gland content of the lesion but its use in the anterior SBDs is limited because of the numerous ducts of Rivinus that are smaller in diameter therefore making the procedure harder to perform. 14 Therefore, the use of different imaging techniques to aid in the final diagnosis of anterior Stafne defects without the need for invasive surgery would be beneficial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Should contrast material be administered, the salivary gland contents of a Stafne bone cavity should enhance to the same degree as the adjacent submandibular gland. 9,12,13 Sialography may also be considered owing to the salivary gland content of the lesion but its use in the anterior SBDs is limited because of the numerous ducts of Rivinus that are smaller in diameter therefore making the procedure harder to perform. 14 Therefore, the use of different imaging techniques to aid in the final diagnosis of anterior Stafne defects without the need for invasive surgery would be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid an unnecessary endodontic treatment, a pulp vitality test should be performed. 13,19,20,26 A residual cyst that develops after the incomplete removal of an inflammatory cyst may mimic SBDs if the lesion is in an edentulous area. Residual cysts tend to expand, displace teeth and cause resorption in the bone unlike SBDs.…”
Section: Discussionmentioning
confidence: 99%
“…It allows definitive diagnosis and can be used in follow-up period. Thus, radiographic follow-up is recommended management for SBC instead of surgery (16).…”
Section: Discussionmentioning
confidence: 99%
“…1 Many other terms have been used to describe this entity, including aberrant or ectopic salivary gland; static, latent or idiopathic defect, cavity or cyst; mandibular salivary gland inclusion; lingual mandibular bone cavity, concavity or depression; and Stafne cyst, defect or cavity. [2][3][4][5][6][7][8][9][10][11] The posterior lingual variant has an incidence of between 0.10% and 0.48% when diagnosed radiologically. However, some cadaver studies have revealed that the incidence of the lesion may be as high as 6.06%.…”
Section: Introductionmentioning
confidence: 99%
“…3,[7][8][9][10] Although the radiological features of SBD have been widely reported, the use of cone beam CT (CBCT) for its diagnosis has been rarely reported. 11 The aim of this article is to clarify the frequency of this phenomenon by using multi-slice CT (MSCT) and CBCT to add to our understanding of the aetiology and content of SBDs by MSCT analysis, and to investigate CBCT use as a tool for exploring SBDs…”
Section: Introductionmentioning
confidence: 99%